Citral condensation with acetone on Na-MgO and Li-MgO catalysts - Jablonski, Estanislao Lorenzo (2006)
The effect of the Na and Li addition to MgO on the pseudo-ionone production from citral and acetone condensation in liquid phase is reported. The Na addition improves the yield to pseudo-ionone (defined as mol of produced pseudo-ionone/mol of converted citral), reaching a value of 100%, while the Li addition has a poor effect. These results can be related to the different distribution of basic sites. It was found that the catalytic activity depends on the acetone/citral and the catalyst/citral ratios. Besides, a poisoning effect of the reaction products on the catalysts was observed, even though the activity of the used catalysts can be partially restored by extraction treatments.